Building a Civilization Base on Spiritual Values: Learning from the Struggle of Husain - Fadhlu Rahman; Anas Amarulloh; Fitri Siska Supriatna (Institut Agama Islam Negeri (IAIN) Curup, 2019)
The modern paradigm gives a strong influence to the modern people especially in the west. The influence is from its coup to the reality of God by some western thinkers and intellectuals. Than it has the impact to the meaning of advance civilization, futher it gives serious problems to the most social structure. The struggle of Sayyidana Husain as the everlasting history of humanity gives another view to the human concept and advance civilization. The oneness values (tauhid) which is contained by al-Husain, look at the spiritual aspects as the measure of the advance civilization. Therfore the definition of advance civilization has a new space, and opens the way of the inherent potentials as the basic of the advance civilization. This writing tries to open the values of Sayyidina Husains struggle in Karbala and mixs it contextually with the concept of Coomaranswammys spiritual civilization as the basic meaning of civilization by using the historical and analysis descriptive method. Hence the paradigm of advance civilization has an alternative of the new paradigm, and the spirituality can be a measure of advance civilization.